A Hydrothermal-Sedimentary Context for the Origin of Life - Westall, F. (Astrobiology, 2018)
Critical to the origin of life are the ingredients of life, of course, but also the physical and chemical conditions in which prebiotic chemical reactions can take place. These factors place constraints on the types of Hadean environment in which life could have emerged. Many locations, ranging from hydrothermal vents and pumice rafts, through volcanic-hosted splash pools to continental springs and rivers, have been proposed for the emergence of life on Earth, each with respective advantages and certain disadvantages. However, there is another, hitherto unrecognized environment that, on the Hadean Earth (4.5–4.0 Ga), would have been more important than any other in terms of spatial and temporal scale: the sedimentary layer between oceanic crust and seawater. Using as an example sediments from the 3.5–3.33 Ga Barberton Greenstone Belt, South Africa, analogous at least on a local scale to those of the Hadean eon, we document constant permeation of the porous, carbonaceous, and reactive sedimentary layer by hydrothermal fluids emanating from the crust. This partially UV-protected, subaqueous sedimentary environment, characterized by physical and chemical gradients, represented a widespread system of miniature chemical reactors in which the production and complexification of prebiotic molecules could have led to the origin of life. Key Words: Origin of life—Hadean environment—Mineral surface reactions—Hydrothermal fluids—Archean volcanic sediments. Astrobiology 18, 259–293.